Design and rhetoric in a Sanskrit court epic : the Kirātārjunīya of Bhāravi - Peterson, Indira Viswanathan, 1950- (State University of New York Press, 2003)
"The Kiratarjuniya is the earlist literary treatment of the narrative of the Pandava hero Arjuna's combat with the great god Siva, a seminal episode in the war epic Mahabharata. Through a close analysis of the structural strategies of Bharavi's poem, the author illuminates the aesthetic of the mahakavya genre. Peterson demonstrates that the classical poet uses figurative language, rhetorical devices, and structural design as the primary instruments for advancing his argument, the reconciliation of heroic action, ascetic self-control, social duty, and devotion to God. Her discussion of the Kiratarjuniya in relation to its historical setting and to rendering of this epic episode in literary texts and temple sculpture of later periods reveals the existence of complex transactions in Indian civilization between the discourses of heroic epic and court poetry, political ideologies and devotional religion, Sanskrit and the regional languages, and classical and folk traditions. Selections from the Kiratarjuniya are presented in poetic translation."--Jacket.